STUDI TENTANG PENGARUH KEMAMPUAN MERESPON PASAR DAN INOVASI PRODUK TERHADAP PENETRASI PASAR PADA KINERJA PEMASARAN (Studi Empiris pada: Industri Rumahan Telur Asin di Kabupaten Brebes) - Mutmainah, Arifia Chamiatun; Soesanto, Harry; Sufian, Syuhada (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
This purpose of this study was to analyze the effect of the ability to respond to market and product innovation to the market penetration in marketing performance. The research’s object which do in this cases are the Salted Egg Home Industry Brebes totaling 102 respondents was conducted by census method.The data analyze technic which used in this case is the structural equation model (SEM) by AMOS. The result showed that research model can be accepted with full structural equation model, index goodness of fit is Chi-Square = 77,930; df = 59; Probability = 0,768; RMSEA = 0,001; GFI = 0,932; AGFI = 0,868; TLI = 1,018; and CFI = 1,000.The conclusion from the results of testing the model is applied to the Home Salted Egg Industry Brebes shows that to gain market penetration in performance marketing is viewed magnitude market sensing to market. Meanwhile, to get market penetration in performance marketing is looking at the magnitude of product innovation. This study provides some of the limitations of the study and future research agenda that can be done in advanced research.